CREANOVA WEBBING: A CREATIVE AND INNOVATIVE WEB-BASED LEARNING TO TEACH CHILDREN’S LITERATURE IN ONLINE CLASSROOM - Eko Heriyanto (Universitas Islam Nahdlatul Ulama Jepara, 2023)
COVID-19 pandemic around the world in 2020–2022 shifted physical learning into distance learning. In Indonesia, particularly since COVID-19 had been announced to disappear, the learning process in several schools still adopts online learning. However, online learning led to certain challenges, one of which relates to the practical method of lecturing to teach children's literature for undergraduate students in universities. This study aims at exploring Creanova Webbing as an alternative method for teaching children’s literature as well as examining the level of respondents' satisfaction with the method. Thus, this research employs qualitative and quantitative methods by describing the implementation of Creanova Webbing, using a questionnaire, and applying the Likert Scale. The findings reveal that the stages of applying Creanova Webbing in the online classroom were the preparation/creation of a website consisting of particular learning material from children’s literature, teaching using the website, and withdrawing feedback from students. In addition, the content of children’s literature on the website is about the relation between Javanese children’s songs and nursery rhymes. Furthermore, the Creanova Webbing belongs to “good” category based scored 68.6% of Likert scale. Further studies are expected to focus on validating and developing the learning materials contained on the website.